Al-Qur’an Sebagai Sumber Ajaran Islam Pertama - Saryadi (MGMP PAI KEPRI, 2022)
The Qur'an is the main source of Islamic teachings and the guiding principle of life for every Muslim. The Qur'an not only contains instructions about the relationship between humans and God, but also regulates human relations with each other, as well as humans with the natural surroundings. To understand the teachings of Islam perfectly, it is necessary to understand the content of the Qur'an and practice it in daily life seriously and consistently. As is known, the Qur'an was revealed in Arabic, both in pronunciation and in uslub. A language rich in vocabulary and meaning. Therefore, it is very important for us to study the study of the Qur'an, so that we can examine more deeply about the verses of the Qur'an as a source of Islamic teachings, both in terms of language, purpose, use, purpose, content that can be used. we apply in life. This article